Avaliação de Impacto das Condicionalidades de Educação do Programa Bolsa Família (2005 e 2009) - Ernesto Friedrich de Lima Amaral; Vinícius do Prado Monteiro (Universidade do Estado do Rio de Janeiro, 2013)
This paper analyzes the impact of the educational conditions of Brazils Bolsa Família Program on the dropout rates of children benefiting from the program. The main hypothesis is that children living in a household that receives the benefit have a lower chance of dropping out of school. Data are from the 2005 and 2009 Impact Evaluation of the Bolsa Família Program (AIBF), collected by the Ministry of Social Development and Combating Famine (MDS), Brazil. Logistic models estimated the chance that children would drop out of school in 2005 and 2009, for three different household income thresholds, taking into account characteristics related to the household, mother, and child. Children who lived in households benefiting from Bolsa Família had a significantly lower chance of dropping out in 2005. Data for 2009 were not statistically significant, although results pointed to a decrease in dropout rates, due to the impact of Bolsa Família.